The Urgency of Implementing Islamic Business Ethics and Islamic Business Management Post-Pandemic on MSMEs - Jumardi Jumardi; Salam Salam; Sabbar Dahham Sabbar; Nurhayani Nurhayani; Hani Amer Musa (IAIN Padangsidimpuan, 2022)
The covid-19 pandemic has reprimanded man with various complex phenomena that have never happened before, both in the fields of health, social, cultural, and economical. In the field of economics, especially the micro, small, and medium sector business actors are mostly paralyzed and on the verge of bankruptcy. This study considers it necessary to examine several aspects of business management, especially MSMEs’ ways of maintaining their business during and after the pandemic. This study aims to examine and analyze the urgency of implementing Islamic business management which can be used as an illustration and guide for business actors. This study uses a descriptive-qualitative approach. The data used is secondary data, referred to as a literature study. The data analysis technique in this study uses three paths, reduction, presentation, and drawing conclusions. The results show that Islamic Business Ethics and Islamic business management are mandatory for business actors so that businesses can run even in the midst of difficult situations. The principles in Islamic business ethics are balance (fairness), free will, responsibility, and truth, while Islamic business management is marketing management, human resource management, and financial management. The results of the study imply that businesses that are run based on Islamic business management principles have the ability to survive and can maintain business continuity. The implementation of ethics and business management within the Islamic framework is very important to be realized by MSMEs actors through their business activities or operations.